The Combination of CD147 and MMP-9 Serum Levels Is Identified as Novel Chemotherapy Response Markers of Advanced Non-Small-Cell Lung Cancer. (24th April 2020) - Qiao, Xiaojuan; Gu, Yan; Yu, Jingfeng; Wang, Jinghui; Liu, Xuan; Gu, Meng; Ma, Li; Jia, Yongfeng; Zhang, Shucai
Abstract : To evaluate the correlation between the changes in serum concentrations of cluster of differentiation-147 (scCD147) and chemotherapy outcome in patients with NSCLC and evaluate the combination of scCD147 with serum matrix metalloproteinase-9 (scMMP-9) levels in the prediction of chemotherapy response, eighty-two patients with advanced LC were enrolled. Newly diagnosed cases were treated with platinum-based chemotherapy. We measured scCD147 protein levels in LC cases by ELISA and used receiver operating characteristic (ROC) curves to analyze the results. Four time points were chosen to examine the association between the changes in scCD147 and chemotherapy outcome: before chemotherapy and 21 days after the start of the first, second, and fourth chemotherapy cycles. We assessed the combination of scCD147 and scMMP-9 serum levels in predicting the chemotherapy response. scCD147 was higher in LC cases than that in healthy volunteers (HVs). scCD147 was associated with distant metastases and TNM stage. scCD147 and scMMP-9 appeared to be independent predictive factors for chemotherapy outcomes after the first and second chemotherapy cycles for patients with NSCLC. Multivariable analysis also demonstrated that variations in scCD147 and scMMP-9 could be independent factors for monitoring chemotherapy outcome for patients with NSCLC. Furthermore, when scCD147 and scMMP-9 are combined into a new risk model, it has a markedly better prediction of chemotherapy outcomes than each protein alone. scCD147 and MMP-9 are potential predictive biomarkers for efficacy, and their combination significantly improves the predictive power for chemotherapy response in patients with NSCLC.